The Effect of Peer Group Support to Psychological Response of Patient With Breast Cancer: A Quasy Experiment - Ilkafah Ilkafah (Indonesian Contemporary Nursing Journal, 2016)
Introduction: Woman with breast cancer oftentimes experience with maladaptive response in against cancer. Peer Group support is one of the most  alternative solution to help women with cancer to get their adaptive response. Goal of this research is to analyze of peer group support influence to  psychological response of patient with breast cancer. Method: Research Design used to pre experimental design. The population were all women with breast cancer at RS Muhammadiyah Lamongan who fulfill inclusion in criteria, sample was recruited using purposive sampling include 16 respondent. The independent variable is Peer Group Support and dependent variable is Psychologys Respons with indicators denial, anger, bargaining, depresi dan acceptance.. Data were collected with questioner and set of activity event (SAK). Data were analyzed using Wilcoxon Signed Rank Test with significance level p £0.00 and mann whitney u test with the significance level p £0.00. Result: the statistical result showen different after peer group support (p = 0.004). Conclusion: This study concluded that peer group support can changed maladaptive psychological response to adaptive psychological response in women suffering from breast cancer, continuous implementation of peer group support in women with breast cancer was suggested to gain better result.